Finite Element Analysis of Tie Beams under the Effect of Differential Settlement of Isolated Footings - Ali Basha; Magdy Salama (Civil Engineering Journal, 2017)
Tie beams that constructed to connect isolated footings are very widely used. The differential settlement between the isolated footings is the main loading case to design the tie beams. In this paper, finite element method is used to determine the straining actions in tie beams under the effect of differential settlement to get clear relations between tie beams straining actions and all the parameters that affect in the design of these tie beams. The parameters included in this paper are the clear length between footings, moment of inertia of tie beam, footings dimensions, soil bearing capacity and the differential settlement value. Charts were presented to show the effect of each parameter in the straining actions of tie beams that can be simply used by design engineers.